A “Wait-and-See” Approach to Quiescent Single-System Langerhans Cell Histiocytosis to Spare Children From Chemotherapy - Oh, Bernice; Lee, Shawn; Ke, Yuhe; Kimpo, Miriam; Yeoh, Allen; Quah, Thuan Chong (Frontiers in Pediatrics, 2020)
Background: Langerhans Cell Histiocytosis (LCH) is a childhood disorder of histiocytes that is generally treated with systemic chemotherapy. Spontaneous resolution has been previously reported in Single System LCH (SS-LCH), which is less aggressive than multisystem disease. However, there are no clear guidelines on which patients can be safely spared from systemic chemotherapy. Here, we propose a risk stratification framework based on disease quiescence as determined by clinical and biochemical features of inflammation, to identify low risk patients who may be potentially spared from chemotherapy through a conservative “wait-and-see” approach. Methods: Retrospective analysis in a single institution was conducted in children with SS-LCH, comparing features of inflammation and outcomes of those who received chemotherapy versus those with quiescent disease, who were managed conservatively. Results: Of 44 children with SS-LCH, only patients without risk-organ involvement were considered for conservative management. A "wait-and-see" approach was adopted for patients with quiescent disease as defined by clinical and biochemical evidence of disease activity. Following 2 weeks of watchful observation, decisions were made to either start treatment or continue conservative management. Based on data collected at diagnosis, patients with quiescent disease had a lower mean platelet count 339x109/L (95%C.I: 285-393) vs 482x109/L (95% C.I: 420-544) p<0.01, a lower mean white cell count 9.3x109/L (95%C.I: 7.5-11.1) vs 13.1x109/L (95%C.I: 11-15.2) p<0.01 and lower Erythrocyte-Sedimentation-Rate (ESR) 8.2mm/hr (95%C.I: 5.4-11) vs 53.7mm/hr (95%C.I: 11-96.3) p=0.04, suggesting that these are potential biochemical markers of disease activity. Other features of disease quiescence noted were rapid progression, functional disability, presence of a skull depression rather a lump and the lack of fever. Conclusions: Further studies are required to validate our proposed framework to determine disease activity in SS-LCH. Within the limits of this current analysis, it appears that low-risk patients with clinically and biochemically quiescent SS-LCH, may potentially be spared from chemotherapy with good long-term outcomes.